Determining the prospects for car rental market in Primorsky Krai (Russia) - Martyshenko, Natalya Stepanovna; Vinichuk, Oksana Yuryevna (International Review of Management and Marketing, 2016)
The paper is devoted to studying the impact of changes in macroeconomic parameters and institutional environment on the development of the car rental market in the regions of Russia. The main purpose of the paper is to draw attention to such a promising area of services market in Primorsky Krai as the car rental. The paper identified the laws and issues related to the organization and development of the car rental market in different regions of Russia. It generalized the experience of car rental business in Europe and the US, systematized the forms of organization and range of services of car rental business in Russia, and analyzed social and economic problems hindering the development of car rental in various regions of Russia. The reasons for the highest growth of the car rental market in Primorsky Krai among the Russian regions were analyzed and systematized. The motives of consumers of car rental services and the factors constraining market development in the region were determined. Car rental market leaders in Primorsky Krai were identified. The range of services of car rental companies and the prices of services in the region were analyzed. The results of the comparative analysis of the cost of the hourly rate for rental and privately owned cars for the different classes are presented. The prospects of development of the car rental market due to new opportunities arising in the transition of Vladivostok to the new status of a free port were determined. There is a need to improve the functioning of the institutional environment of the car rental business to develop the business in the region. Keywords: regional economy, free port, car business, car rental market, services market infrastructure JEL Classifications: D40, M10